2008
DOI: 10.1007/s10327-008-0075-7
|View full text |Cite
|
Sign up to set email alerts
|

HrpG regulates type II secretory proteins in Xanthomonas axonopodis pv. citri

Abstract: HrpG, a two-component response regulatorlike protein, is a key regulator of the type III secretion system (T3SS) in Xanthomonas spp. In X. campestris pv. vesicatoria, HrpG with a single amino acid substitution (HrpG*) gains the ability to induce the expression of T3SS-related genes even under nutrient-rich conditions. In this study, we investigated the role of HrpG in the synthesis of the secretory protein using HrpG* in strain NA-1 of X. axonopodis pv. citri (Xac NA-1), a causal agent of citrus canker. Eleven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 42 publications
4
52
0
1
Order By: Relevance
“…Even though the two-component system has been suggested to play crucial roles in multiple cellular functions of X. citri subsp. citri, only a few have been studied for their contributions to virulence, such as HrpG (46). In this study, we present evidence that the two-component system ColR/ColS plays important roles in the virulence, growth in planta, biofilm formation, lipopolysaccharide (LPS) production, catalase activity, and environmental stress resistance of the citrus canker pathogen X. citri subsp.…”
mentioning
confidence: 91%
“…Even though the two-component system has been suggested to play crucial roles in multiple cellular functions of X. citri subsp. citri, only a few have been studied for their contributions to virulence, such as HrpG (46). In this study, we present evidence that the two-component system ColR/ColS plays important roles in the virulence, growth in planta, biofilm formation, lipopolysaccharide (LPS) production, catalase activity, and environmental stress resistance of the citrus canker pathogen X. citri subsp.…”
mentioning
confidence: 91%
“…The regulation of hrp genes might be influenced by plant-inducing factors that occur owing to the presence of a plant-inducible promoter known as PIP box [TTCGC (N 15 ) TTCGC], as well as the nutritional conditions of the medium (Leach and White, 1996;Da Silva et al, 2002). Yamazaki et al (2008) have suggested the presence of an imperfect PIP box for the CPXAC gene. By contrast, pathogenicity genes hrpX and hrpG are responsible for the secretion of proteins in type III and some type II systems (Sandkvist, 2001;Furutani et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The secretion products from Xac have been described by Yamazaki et al (2008), who reported the presence of an extracellular cysteine peptidase secreted by Xac (strain NA-1) cultivated in medium that induced hrp and hypersensitivity genes. The N-terminal region of this secreted cysteine peptidase was sequenced and generated AVHGMGLKPSSLMQPV, which is identical to the sequence from HIS CPXAC (after the 25th residue).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations